2017
DOI: 10.1136/bmjopen-2017-018048
|View full text |Cite
|
Sign up to set email alerts
|

Charcot-Marie-Tooth disease in Denmark: a nationwide register-based study of mortality, prevalence and incidence

Abstract: ObjectivesCharcot-Marie-Tooth disease (CMT) is the most common inherited disorder of the peripheral nervous system, yet no studies have compared the mortality in patients with CMT with that of the general population, and prevalence estimates vary considerably. We performed a nationwide register-based study to investigate the prevalence, incidence and mortality of CMT in Denmark.DesignWe used the Danish National Patient Registry to select all records with primary diagnostic codes for CMT between 1977 and 2012 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
(33 reference statements)
4
9
0
1
Order By: Relevance
“…The age-standardized prevalence of CMT in 2018 was slightly higher in men than in women, confirming previous results [11,17]. The prevalence in men was higher at all ages but was especially higher in men than in women aged 15-35 years.…”
Section: Discussion/conclusionsupporting
confidence: 87%
See 3 more Smart Citations
“…The age-standardized prevalence of CMT in 2018 was slightly higher in men than in women, confirming previous results [11,17]. The prevalence in men was higher at all ages but was especially higher in men than in women aged 15-35 years.…”
Section: Discussion/conclusionsupporting
confidence: 87%
“…Determinations of age-specific SMR showed that the mortality rate was particularly high in children diagnosed with CMT at a young age. A similar finding was reported in a study performed in Denmark, the only previous study investigating the age-specific mortality of CMT patients [11]. Moreover, patients with Déjerine-Sottas disease, a type of early-onset CMT, showed severe disability and poor prognosis [21].…”
Section: Discussion/conclusionsupporting
confidence: 84%
See 2 more Smart Citations
“…Attempts to determine the prevalence of CMT have yielded in a range of estimates from different places in the world-from 9.7 per 100,000 in Serbia, to 82.3 per 100,000 in Norway and 22.5 per 100,000 in Denmark [2]. The prevalence of the disease subtype is known to vary by region as well, with CMT type 1A being most common in Western regions and the other forms more frequent in the Asian population [3].…”
Section: Introductionmentioning
confidence: 99%